Social risk management as a strategy in the fight against poverty and social exclusion - Hana Vykopalová (DANUBE: Law, Economics and Social Issues Review, 2016)
Questions surrounding the fight against poverty and social exclusion have become a global priority. Poverty and its causes are perceived as differences in the economic and social development of each individual continent and country. Social risk management was developed by the World Bank as a specific conceptual framework of social protection strategy and includes prevention, mitigation and the management of social risks. The diverging causes of poverty across the European continent assume a different approach in identifying causes and social risk management. An important aspect of the EU's social policy is to combat unemployment and social exclusion with the support of the European fund to help the extreme poor and other EU funds, e.g. EQUAL. The appropriate implementation of social risk management in each country is a prerequisite for reducing extreme poverty. Social risk management as a global strategy to combat poverty and extreme poverty is a challenge in the field of education which offers a new range of views and is generating more complex professional competencies in education and new possibilities for university graduates in the labor market.
Keywords: 330; Social Exclusion; Poverty; Sources of Social Risks; Strategies to Combat Poverty; Social Risk Management